Analisis Pengaruh Peminatan Jurusan Ekonomi Manajemen terhadap Bidang Kerja Lulusan: Studi Kasus Lulusan Jurusan Ekonomi Manajemen Universitas Bina Nusantara Tahun 2000 – 2004 - Antonius Herusetya; Hartiwi Prabowo; Synthia Atas Sari (Bina Nusantara University, 2006)
Article explore whether there is influences on choice of management department to the workforce absorpation by company as consumer of labour.Technique analysis data use Chi-Quadrat to know influence between program enthusiasm and work all graduated. The research result indicates that there is significant influence between enthusiasm majors with job area entered by Faculty of Economics, Majors Management, UniversityBina Nusantara. Enthusiasm Majors Management in this time still relevant with work all graduated (77.2%), specially marketing and entrepreneurship (92%).